Encefalopatías espongiformes transmisibles : biología del prion y estado actual de la vigilancia epidemiológica en Colombia (2010)
ABSTRACT: Transmissible Spongiform Encephalopaties, also called prion diseases, are a group of neurodegenerative diseases affecting a variety of mammals. The responsible agent consists of an abnormal isoform of a cellular protein that suffers a conformational change (prion), acquiring the ability of being transmissible. It has been demonstrated prions capacity to cross the species barrier between the cattle and humans; affecting public health in countries with reported cases of bovine spongiform encephalopathy. The transmissible spongiform encephalitis have been reported in a number of countries and Colombia is not the exception with some human sporadic cases, not related with the intake of contaminated material from sick animals. With this manuscript we pretend to give a view of the history and the current state of prion diseases in Colombia, which represent a serious threat for the public health and the cattle industry of the country.